A Time-Dependent Double Hardening Model for Soft Rock. (7th October 2019) - Siddiquee, Mohammed Saiful Alam; Hamdi, Amin
Abstract : The time-dependent behavior of soft rock is very important in tunnel construction through soft rock. There is always a chance of creep failure due to sustained loading along the crest of the tunnel. In this research, a three-component elasto-visco-plastic framework is used to develop a time-dependent double hardening model to predict the behavior of soft rock both in compression and shear. Due to the limitation of time-dependent single yield hardening model in predicting the behavior of soft rock in compression direction (volumetric deformation) of loading, another time-dependent yield surface is added to the compression direction. The intersection of two-yield surface usually gives rise to singularity phenomenon, which is avoided by using Koiter's generalization principle. A new formulation of the stress-integration of incremental stress-strain equations is proposed. A series of triaxial compression tests were carried out at different strain rates to calculate the model parameters. Then, the model is used to simulate the various behavioral features of soft rock.